2014
DOI: 10.1021/ac403845u
|View full text |Cite
|
Sign up to set email alerts
|

Development and Quantitative Evaluation of a High-Resolution Metabolomics Technology

Abstract: Recent advances in mass spectrometry have allowed for unprecedented characterization of human metabolism and its contribution to disease. Despite these advances, limitations in metabolomics technology remain. Here, we describe a metabolomics strategy that consolidates several recent improvements in mass spectrometry technology. The platform involves a high-resolution Orbitrap mass spectrometer coupled to faster scanning speeds, allowing for polarity switching and improved ion optics resulting in enhanced sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
205
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(208 citation statements)
references
References 36 publications
2
205
0
Order By: Relevance
“…Tregs can also induce dendritic cells to consume essential amino acids, which inhibits T cell proliferation (35 Metabolomics and acyl-carnitines. Nontargeted metabolomic analyses were performed as described using LC Q Exactive Mass Spectrometer (LC-QE-MS) (Thermo Scientific) (24). Additional metabolomics analysis was performed using GC/MS and LC/MS/MS platforms (Metabolon Inc.) for determination of cellular metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tregs can also induce dendritic cells to consume essential amino acids, which inhibits T cell proliferation (35 Metabolomics and acyl-carnitines. Nontargeted metabolomic analyses were performed as described using LC Q Exactive Mass Spectrometer (LC-QE-MS) (Thermo Scientific) (24). Additional metabolomics analysis was performed using GC/MS and LC/MS/MS platforms (Metabolon Inc.) for determination of cellular metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore examined metabolite levels and metabolic gene expression of Th1 and Th17 cells and Tregs in detail, as the balance of these subtypes is crucial in a variety of inflammatory settings. Unsupervised clustering of steady-state levels of approximately 400 metabolites measured by high-resolution nontargeted Q exactive-mass spectrometry (QE-MS) metabolomics (24) showed that Teffs and Tregs had broad metabolic differences ( Figure 4A and Supplemental Table 1). Importantly, Tregs were dissimilar from Th1 and Th17 cells, which clustered together.…”
Section: Inhibition Of Glycolysis or Mitochondrial Oxidation Selectivmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/259523 doi: bioRxiv preprint first posted online Feb. 4, 2018; method (HILIC) with an Xbridge amide column (100 x 2.1 mm i.d., 3.5 µm; Waters) was used for compound separation at room temperature. The mobile phase and gradient information were described previously 45 . 2-hydrazinoquinoline derivatives were measured using reversed phase LC method, which employed an Acclaim RSLC 120 C8 reversed phase column (150 x 2.1 mm i.d., 2.2 µm; Dionex) with mobile phase A: water with 0.5 % formic acid, and mobile phase B: acetonitrile.…”
Section: Disclosuresmentioning
confidence: 99%
“…We therefore developed a novel method for sensitive, rapid, and quantitative acyl-CoA profiling, with a compatible sample preparation procedure that has been previously shown for polar metabolite analysis (18). The method involves LC-MS using reversed phase chromatographic separation coupled to a high-resolution Orbitrap mass spectrometer with label free quantitation.…”
mentioning
confidence: 99%